2022
DOI: 10.1038/s41598-022-19141-4
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0047339 promotes the activation of fibroblasts and affects the development of urethral stricture by targeting the miR-4691-5p/TSP-1 axis

Abstract: Urethral stricture is related to scar tissue fibrosis, but its pathogenesis is still unclear. This study aims to explore the regulatory mechanism of circular RNA (circRNA) in the occurrence and development of urethral stricture. CircRNA microarray was employed to analyze circRNA expression profiles between human urethral scar tissue and normal urethral tissue. The results of circRNA microarray showed that there were 296 differentially expressed genes between urethral scar tissue and normal urethral tissue. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…They can interact with the 3′ untranslated regions (3′UTRs) of downstream target messenger RNAs (mRNAs), consequently destabilizing mRNAs or repressing translation 22 . Several miRNAs have been indicated to participate in regulating the progression of US, such as miR‐146a, miR‐4691‐5p, and let‐7i‐5p 4,23,24 . Intriguingly, a recent study demonstrated that miR‐486 was prominently downregulated after urethral injury 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can interact with the 3′ untranslated regions (3′UTRs) of downstream target messenger RNAs (mRNAs), consequently destabilizing mRNAs or repressing translation 22 . Several miRNAs have been indicated to participate in regulating the progression of US, such as miR‐146a, miR‐4691‐5p, and let‐7i‐5p 4,23,24 . Intriguingly, a recent study demonstrated that miR‐486 was prominently downregulated after urethral injury 25 .…”
Section: Introductionmentioning
confidence: 99%
“… 22 Several miRNAs have been indicated to participate in regulating the progression of US, such as miR‐146a, miR‐4691‐5p, and let‐7i‐5p. 4 , 23 , 24 Intriguingly, a recent study demonstrated that miR‐486 was prominently downregulated after urethral injury. 25 Nonetheless, it is unclarified whether miR‐486 has an effect on the development of US.…”
Section: Introductionmentioning
confidence: 99%
“…The formation and recurrence of urethral strictures are related to the formation of fibrosis in the healing process of the injured tissue, which is mainly related to the excessive deposition of extracellular matrix (ECM) in the submucosa of the urethra, an increase in collagen level, a change in the proportion of collagen types I and III, and an imbalance in ECM degradation (Hughes et al, 2020;Feng et al, 2021). Similar to many fibrosis-related diseases, abnormal expression of fibroblast genes in urethral tissues is believed to be a major cause of scarring (Ding et al, 2022). Transforming growth factor β1 (TGF-β1) is an effective chemokine of fibroblasts and an important mediator of fibrosis, as it induces the production and secretion of collagen by fibroblasts, thereby causing tissue fibrosis (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%